2009
DOI: 10.1088/0031-9155/54/14/n01
|View full text |Cite
|
Sign up to set email alerts
|

Breathing interplay effects during proton beam scanning: simulation and statistical analysis

Abstract: Treatment delivery with active beam scanning in proton radiation therapy introduces the problem of interplay effects when pencil beam motion occurs on a similar time scale as intra-fractional tumor motion. In situations where fractionation may not provide enough repetition to blur the effects of interplay, repeated delivery or 'repainting' of each field several times within a fraction has been suggested. The purpose of this work was to investigate the effectiveness of different repainting strategies in proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
208
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(212 citation statements)
references
References 14 publications
4
208
0
Order By: Relevance
“…This assumption could lead to the possibility of systematic error, as shown by Evans et al 12 Furthermore, since in practice there is no practical way to determine f ( x) for an individual patient, the "weighted average of the dose distribution without motion" is often further approximated by the dose distribution without motion or the 3D static dose. 13 With the availability of 4D respiration-correlated computer tomography (CT) and deformable registration, 4D accumulated dose (4D dose) distribution calculation can be performed with the tumor motion being correlated with time (f ( x, t)) or phase (f ( x, n)). Studies have shown that the 4D dose can differ significantly from the 3D static dose, calculated on any single-phase or average CT, for both photon 14,15 and scanning beam proton 16,17 radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption could lead to the possibility of systematic error, as shown by Evans et al 12 Furthermore, since in practice there is no practical way to determine f ( x) for an individual patient, the "weighted average of the dose distribution without motion" is often further approximated by the dose distribution without motion or the 3D static dose. 13 With the availability of 4D respiration-correlated computer tomography (CT) and deformable registration, 4D accumulated dose (4D dose) distribution calculation can be performed with the tumor motion being correlated with time (f ( x, t)) or phase (f ( x, n)). Studies have shown that the 4D dose can differ significantly from the 3D static dose, calculated on any single-phase or average CT, for both photon 14,15 and scanning beam proton 16,17 radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…scanning repetitively within one fraction [8]. A number of repainting schemes have been investigated previously [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is the same for both scattering and scanning delivery techniques. In addition, for active scanning, the major effect of intrafield motion is ''interplay'', which relates to motion, usually respiratory motion, with a frequency similar to that of the scanned beam, and which can lead to overand underdosage in the target volume [34][35][36][37].…”
Section: Motionmentioning
confidence: 99%
“…The problem of organ motion and rescanning synchronism has also been tackled by several groups, including Furukawa et al [45] and Seco et al [37]. Solutions include: N using random modulations, e.g.…”
Section: Rescanningmentioning
confidence: 99%